Simon birch - Mark, Laurence; Birnbaum, Roger; Johnson, Mark Steven ([S.l.] : Hollywood Pictures [production company] ; Kuala Lumpur : Berjaya HVN Sdn. Bhd. [distributor])
A heartwarming and funny hit that's earned overwhelming critical acclaim, Simon Birch features great performances from stars Ashley Judd and Oliver Platt in an outstanding cast.
Executive producer, John Baldecchi ; screenplay, John Irving, editor, David Finfer
Cast: Joseph Mazzello, Oliver Platt, Ian Michael Smith, Ashley Judd
Keywords: Irving, John, -- 1942- -- Film and video adaptations; Children in motion pictures; Friends -- Drama